Immune Recovery Following Autologous Hematopoietic Stem Cell Transplantation in HIV-Related Lymphoma Patients on the BMT CTN 0803/AMC 071 Trial - Shindiapina, Polina; Pietrzak, Maciej; Seweryn, Michal; McLaughlin, Eric; Zhang, Xiaoli; Makowski, Mat; Ahmed, Elshafa Hassan; Schlotter, Sarah; Pearson, Rebecca; Kitzler, Rhonda; Mozhenkova, Anna; Le-Rademacher, Jennifer; et al. (Frontiers in Immunology, 2021)
We report a first in-depth comparison of immune reconstitution in patients with HIV-related lymphoma following autologous hematopoietic cell transplant (AHCT) recipients (n=37, lymphoma, BEAM conditioning), HIV(-) AHCT recipients (n=30, myeloma, melphalan conditioning) at 56, 180, and 365 days post-AHCT, and 71 healthy control subjects. Principal component analysis showed that immune cell composition in HIV(+) and HIV(-) AHCT recipients clustered away from healthy controls and from each other at each time point, but approached healthy controls over time. Unsupervised feature importance score analysis identified activated T cells, cytotoxic memory and effector T cells (higher in HIV(+)), and naïve and memory T helper cells (lower HIV(+)) as a having a significant impact on differences between HIV(+) AHCT recipient and healthy control lymphocyte composition (p<0.0033). HIV(+) AHCT recipients also demonstrated lower median absolute numbers of activated B cells and lower NK cell sub-populations, compared to healthy controls (p<0.0033) and HIV(-) AHCT recipients (p<0.006). HIV(+) patient T cells showed robust IFN production in response to HIV and EBV recall antigens. Overall, HIV(+) AHCT recipients, but not HIV(-) AHCT recipients, exhibited reconstitution of pro-inflammatory immune profiling that was consistent with that seen in patients with chronic HIV infection treated with antiretroviral regimens. Our results further support the use of AHCT in HIV(+) individuals with relapsed/refractory lymphoma.